An efficient, four-component reaction for the synthesis of novel carbamodithioates. (2nd January 2017) - Sadat-Ebrahimi, Seyed Esmail; Karim, Leila; Moghimi, Setareh; Yahya-Meymandi, Azadeh; Mahdavi, Mohammad; Vosooghi, Mohsen; Foroumadi, Alireza; Shafiee, Abbas
ABSTRACT: A series of substituted phenylcarbamoyl methyl benzylcarbamodithioates have been synthesized using the multicomponent condition. The reaction proceeded under mild practical condition and afforded the desired products in good yields. GRAPHICAL ABSTRACT: